Assessing organizational performance in higher education - Miller, Bárbara A.
Aimed at faculty, staff, and administrators at colleges and universities, this text presents an approach to organizational performance evaluation that is rooted in systems theory. Consultant Barbara Miller's conceptual framework goes beyond the assessment of student outcomes to evaluate performance in seven broad organizational areas. A number of photocopiable worksheets are provided to aid in the assessment process. In the final chapter, Miller explains how to build and deploy campus-wide assessment programs. Jossey-Bass is an imprint of Wiley. The book provides a full complement of assessment technologies that enable leaders to measure and evaluate performance using qualitative and quantitative performance indicators and reference points in each of seven areas of organizational performance. While these technologies are not new, applying them in a comprehensive assessment of the performance of both academic and administrative organization in higher education is a true innovation. Assessing Organizational Performance in Higher Education defines four types of assessment user groups, each of which has unique interest in organizational performance. This offers a new perspective on who uses performance results and why they use them. These varied groups emphasize that assessment results must be tailored to fit the needs of specific groups, that ?one-size-fits-all? does not apply in assessment. An assessment process must be robust and capable of delivering the right information at the right time to the right user groupáginas: